Barriers of culture, networks, and language in international migration: A review - Zhiling Wang; Thomas de Graaff; Peter Nijkamp (REGION, 2018)
Along with the increasing pace of globalization, recent decades faced a dramatically increase in international migrant flows as well. Compared to the flows of trade, capital and knowledge, we observe that contemporaneous complex institutional differences, historical backgrounds, and individuals' diverse socio-demographic characteristics make the migrant workers' choice of destination arguably much more uncontrollable. This study shows that migration is in a complex way intertwined with culture, networks and language, (i) by reviewing related studies on the barriers of culture, networks and language in international labor mobility, and (ii) by exploring missing gaps and prospective avenues for research. Nowadays, the migration pressure on Europe and the United states has created substantial challenges, leading to an urgent need to address the economic assimilation and social integration of migrants. Against this background, we emphasize that these non-economic factors have played an increasingly critical role in shaping international migration and its future socio-economic consequences for destination countries.
Keywords: F22; Z10; Z13; 330; migration; culture; networks; language